1979
DOI: 10.1111/j.1365-2125.1979.tb00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind Evaluation of the Safety and Hypnotic Efficacy of Temazepam in Insomniac Outpatients

Abstract: 1 Efficacy of temazepam 30 mg at night as an hypnotic was compared with placebo in 55 out-patients with insomnia. The study was double blind, with two comparable groups of patients established by random allocation. Placebo and medication were taken for 4 consecutive nights and sleep questionnaires were completed the next day. 2 Patients reported that temazepam was more effective than placebo in reducing the difficulty of falling asleep and improving sleep maintenance. They also indicated that they awoke less a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The effect of temazepam was similar to that of flurazepam in its efficacy and its effect on slow wave sleep (Dement, Carskadon, Mitler, Phillips & Zarcone, 1978), but flurazepam also suppressed REM sleep (Kales, Kales, Bixler & Slye, 1971;Kales, Kales, Bixler & Scharf, 1975). In outpatients with insomnia, Heffron & Roth (1979) and Fillingim (1979) have found that temazepam 30 mg increased total sleep time, reduced difficulty in falling asleep and improved sleep with less awakenings, particularly in the early morning.…”
Section: Effectiveness In Insomniamentioning
confidence: 97%
“…The effect of temazepam was similar to that of flurazepam in its efficacy and its effect on slow wave sleep (Dement, Carskadon, Mitler, Phillips & Zarcone, 1978), but flurazepam also suppressed REM sleep (Kales, Kales, Bixler & Slye, 1971;Kales, Kales, Bixler & Scharf, 1975). In outpatients with insomnia, Heffron & Roth (1979) and Fillingim (1979) have found that temazepam 30 mg increased total sleep time, reduced difficulty in falling asleep and improved sleep with less awakenings, particularly in the early morning.…”
Section: Effectiveness In Insomniamentioning
confidence: 97%
“…Temazepam in the hard capsule formulation available in the United States has been shown in double-blind, placebo controlled, clinical trials to relieve complaints of difficulty falling asleep, frequent awakenings, and early morning awakenings (Fillingim, 1979(Fillingim, , 1982Heffron & Roth, 1979). However, three sleep laboratory studies, while demonstrating temazepam's overall hypnotic efficacy, did not confirm the perception of reduced sleep latency found in the clinical trials (Bixler et al, 1978;Mitler et al, 1979;Vogel, 1983, personal communication).…”
Section: Introduction Methodsmentioning
confidence: 82%
“…Outcomes included patient-reported estimates of SL, TST, NOA and QOS. Heffron 115 reported on 55 "insomnia outpatients" who received temazepam 30 mg or placebo in parallel groups for four nights. Subjects reported SL, TST, NOA and QOS.…”
Section: -112mentioning
confidence: 99%
“…Two studies 114,115 reported subjective NOA at 30 mg. They found −1.0 and −1.24 awakenings, respectively, compared to placebo.…”
Section: Number Of Awakeningsmentioning
confidence: 99%